Pengembangan Media Komik Petualangan untuk Meningkatkan Keterampilan Menulis Cerita Fantasi Kelas VII MTs Negeri 2 Medan - Mayang Serungke; Tri Indah Kusumawati; Budiman Budiman (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
The research that has been conducted is entitled "Development of Adventure Comic Media to Improve Fantasy Story Writing Skills of Class VII MTs Negeri 2 Medan", the background of this research is the low writing ability of students, which is caused by difficulties in developing ideas and the use of conventional learning methods. This problem encouraged researchers to develop learning media in the form of comics as an innovative alternative to support more interesting and effective learning. This research uses the ADDIE development model which consists of five stages, namely analysis, design, development, implementation, and evaluation. Data were obtained through questionnaires, interviews, observations, tests, and documentation, and involved a validation process by material experts, media experts, and linguists. Furthermore, trials were conducted on students of class VII-G as an experimental class. The results of the study showed that the developed adventure comic media was classified as very feasible, practical, and effective. The validation results by three experts showed that the media expert gave a score of 95% (after revision), the material expert 98.33%, and the linguist 88%. In addition, user responses to the media were also very positive. Students in class VII-G gave an assessment of 94,52%, while the teacher gave an assessment of 97.14%. All assessment results are included in the very practical category. In terms of effectiveness, pretest and posttest tests were conducted to measure the improvement of students' writing skills. The results of the effectiveness trial were analyzed using the N-Gain value. In class VII-F (control class), the N-Gain score was 48.66%, while in class VII-G (experimental class) it was 68.35% with a fairly effective category. These results indicate that adventure comic media is quite effective in improving students' fantasy story writing skills. Thus, adventure comic media can be used as an alternative learning media that is interesting, easy to understand, and able to increase students' motivation and writing skills, especially in fantasy story text material.